HEAVY METAL LEVELS IN THREE MAJOR CARPS (CATLA CATLA, LABEO ROHITA AND CIRRHINA MRIGALA) FROM THE RIVER RAVI, PAKISTAN - A. RAUF, M. JAVED AND M. UBAIDULLAH (Pakistan Veterinary Journal, 2009)
The present study was conducted to determine heavy metal (cadmium and chromium) concentrations in gills, kidneys, liver, skin, muscles and scales of three fish species (Catla catla, Labeo rohita and Cirrhina mrigala) from three stations viz. Lahore Siphon (Up stream), Shahdera Bridge and Baloki Headworks (Down stream) in the river Ravi, Pakistan. Heavy metal concentrations varied significantly depending upon the type of fish tissues and locations. The concentrations of cadmium and chromium differed significantly (p<0.001) among five fish organs and three sites and non-significantly between the three fish species. Fish liver appeared to have significantly higher tendency for the accumulation of cadmium and chromium (4.26 ± 1.57 and 6.23 ± 1.14 µgg-1), while gills had minimum concentrations (1.10 ± 0.53 and 1.46 ± 0.52 µgg-1) of these metals. Generally, Catla catla showed higher levels of metal concentrations than Labeo rohita and Cirrhina mrigala. Metal contamination was highest at Baloki Headworks, probably due to inclusion of more effluents from industrial and sewage water.